The question of animal selves: Implications for sociological knowledge and practice - Irvine, Leslie (Qualitative Sociology Review, 2007)
The question of whether sociologists should investigate the subjective experience of non-human others arises regularly in discussions of research on animals. Recent criticism of this research agenda as speculative and therefore unproductive is examined and found wanting. Ample evidence indicates that animals have the capacity to see themselves as objects, which meets sociological criteria for selfhood. Resistance to this possibility highlights the discipline’s entrenched anthropocentrism rather than lack of evidence. Sociological study of the moral status of animals, based on the presence of the self, is warranted because our treatment of animals is connected with numerous “mainstream” sociological issues. As knowledge has brought other forms of oppression to light, it has also helped to challenge and transform oppressive conditions. Consequently, sociologists have an obligation to challenge speciesism as part of a larger system of oppression.